Building High-performance Teams in Pediatric Orthopaedic Surgery: The Importance of Psychological Safety and Creating a Trusting Environment - Steven L. Frick, MD; Virginia F. Casey, MD; Benjamin J. Shore, MD MPH FRCSC; Peter M. Waters, MD MMSc (Elsevier, 2024)
Pediatric orthopaedic surgeons are the central figures in the delivery of specialized musculoskeletal care for children. Our work transcends individual skills, relying heavily on high-performance teams (HPTs) of professionals who deliver care cohesively across ambulatory clinics, hospital, and operating room settings. Furthermore, collaboration with hospital administrators is essential to secure the people, buildings, equipment, and resources for successful long-term patient care strategies. Thus, every pediatric orthopaedic surgeon needs to develop leadership skills that facilitate optimal patient care by creating a work environment that promotes peak performance by all team members. This article explores the foundational elements necessary to build and sustain HPTs in pediatric orthopaedic surgery, with a particular emphasis on psychological safety and trust. We will also provide recommendations for promoting a culture of excellence and mutual care.